How Hobby Becomes Occupation in Creative Economy - АлимовАлександр Алексеевич (Journal of Economic Sociology, 2018)
This paper is devoted to studying the process of transformation of a hobby into an occupation in the creative economy, specifically in the case of streamers of gaming content. In particular, the main strategies, the prerequisites, and the consequences of deciding to monetize activities and turn leisure practices into a source of income are considered. The purpose of this work was to identify socially determined problems in the process of transforming a hobby into an occupation. For this, 15 semi-structured interviews with streamers and producers of gaming content were conducted and analyzed, which allowed the features and mechanisms of transformation to be determined. As a result, changes in the subjective perception of monetized leisure practices were determined and the main factors contributing to the changes were identified. The roles of the platform, the audience, and professional standards in the process of hobby transformation were also discovered. A further result was the identification of the process accompanying transformation: formalization, defined as the integration of hobbies into external institutional frameworks; commodification, defined as the emergence of practices for the reification of emotional aspects of streamer activity and the implementation of practices for their evaluation and sale; economization, defined as the reorganization of the structure of activities to maximize earnings; and marketization, defined as orientation to the audience and delegation of opportunities for viewers to partially define the structure of activities